Pengaruh Mikro dan Makro Ekonomi Terhadap Harga Saham pada Industri Perkebunan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Riski Pitriani (Science of Management and Students Research Journal (SMS), 2019)
This research is descriptive quantitative research and the analytical tool used in this study is multiple linear regression using panel data which is useful to see the direction of the relationship between dependent variables to free. To answer the number one goal, a statistical test is used i.e the F test and to answer the goal number 2, a statistical test is used i.e t test. Correlation coefficient to find out how the relationship between variables and coefficient of determination is useful to see the magnitude of the influence of the dependent variable on free.The history of plantations in developing countries, especially Indonesia, cannot be separated from the history of the development of colonialism, capitalism and modernization. The plantation system is part of the commercial and capitalistic agricultural economic system. The plantation system has introduced a variety of reforms in the agricultural economic system that have an important impact on the lives of developing countries.SPSS 20 results get multiple linear regression using panel data equation is Log Y = 9,019 - 2,242 Log X1it - 1,095 Log X2 it + 0,380 Log X3it - 0,225 Log X4it + 0,225 Log X5it - 1,174 Log X6it + e. From the results obtained by SPSS (coefficient) r2 this number is 0.893, meaning the percentage contribution of the influence of variables Current Ratio (CR), Debt Equity Ratio (DER), Return On Equity (ROE), Price Earning Ratio (PER), Inflation and Oil Prices The World of Stock Prices is 89.3%. While the remaining 10.7% is influenced by other variables not included in this model.Simultaneously that Current Ratio (CR), Debt Equity Ratio (DER), Return On Equity (ROE), Price Earning Ratio (PER), Inflation and World Oil Prices together influence stock prices and partially CR and DER affect the temporary share price of ROE PER, inflation and world oil prices did not affect the stock price of the plantation industry listed on the Indonesia Stock Exchange in the 2013-2017 period.